Faktor Risiko Stunting, Anemia Defisiensi Besi, dan Koeksistensinya pada Anak Usia 6-9 Tahun di Indonesia: Hasil dari Indonesian Family Life Survey (IFLS-5) tahun 2014-2015: Risk Factors of Stunting, Iron Deficiency Anemia, and Their Coexistence among Children Aged 6-9 Years in Indonesia: Results from the Indonesian Family Life Survey-5 (IFLS-5) in 2014-2015 - Mia Mustika Hutria Utami; Lilik Kustiyah; Cesilia Meti Dwiriani (Universitas Airlangga, 2023)
Background: Stunting and anemia are malnutrition and have become major public health problems. The evidence is limited about the coexisting stunting and anemia (CSA) among school-aged children (SAC). Objectives: To analyze risk factors of stunting, anemia, and their coexistence among Indonesian children aged 6-9. Methods: This cross-sectional study used secondary data from 1,986 children aged 6-9 years from 13 out of 34 provinces in Indonesia. Risk factors of stunting, anemia, and CSA were analyzed by logistic regression. Results: The prevalence of stunting, anemia, and CSA among children aged 6-9 years was 24.8%, 30.5%, and 8.8%, respectively. Risk factors of stunting were anemia (OR=1.355), underweight father (OR=1.587), maternal education (<12 years) (OR=1.679), short parental stature (mother: OR=2.504, father: OR=1.995), low and middle sanitation score (OR=2.356, OR=1.366), and living in a rural area (OR=1.367). Risk factors of anemia were stunting (OR=1.307), age 6-7 years (OR=1.933), and parental anemia (mother: OR=1.973, father: OR=1.692). Children aged 6-7 years (OR=1.993) and short parental stature (mother: OR=1.901, father: OR=1.620) were risk factors for CSA. Conclusions: The coexistence of stunting and anemia as a double burden of undernutrition exists among Indonesian children. An anemic child, an underweight father, low maternal education, low and middle sanitation score, and living in a rural area increase the risk of stunting. Stunted children and parental anemia increase the risk of anemia, short parental stature increases the risk of stunting and CSA, while younger children increase the risk of anemia and CSA.